Kesejahteraan Psikologis Sebagai Prediktor Kepatuhan Pengobatan: Studi Pada Penderita Hipertensi Di Puskesmas Medokan Ayu Surabaya - Nur Muji Astuti; Yenny Setya Wigaty; Lela Nurlela (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Hypertension is known as silent killer because it often causes no symptoms, it carries the risk of various complications. Hypertension management requires long-term treatment with a high level of adherence. Psychological well-being is a factor influencing medication adherence. Good psychological well-being can improve motivation, emotional regulation, and an individual's ability to consistently adhere to treatment. Objective: to analyze the prediction of psychological well-being and medication adherence in hypertension patients at the Medokan Ayu Community Health Center in Surabaya Methods: This study used correlational analytical design with a descriptive approach.cross sectional. The population in this study was all hypertension sufferers at the Medokan Ayu Community Health Center in Surabaya with a sample size of 133 respondents using random sampling technique. The research instrument was a questionnaire Scales Of Psychological Well-Being(SPWB-18) and Morisky Medication Adherence Scale(MMAS-8). Data analyzed using Spearman Rank test. Results: The results showed that 85% of respondents had high psychological well-being and 72.9% had high medication adherence. The Spearman Rank test showed a p-value of 0.000 (p < 0.05) with a correlation coefficient of r = 0.491, indicating a positive relationship with moderate strength Conclusion: Good psychological well-being allows people with hypertension to be more compliant with their treatment. Support from family and healthcare professionals use a crucial role in improving psychological well-being, ensuring patients feel supported and motivated to maintain optimal medication adherence